Building a pentesting lab for wireless networks : build your own secure enterprise or home penetration testing lab to dig into the various hacking techniques /: build your own secure enterprise or home penetration testing lab to dig into the various hacking techniques. (2016) - Fadyushin, Vyacheslav; Popov, Andrey
No abstract available